clodbuff
clodbuff
10-05-2018
Mathematics
contestada
f(x)=3x-2 and g(×)=2x-1, then g(f(x))=?
Respuesta :
Аноним
Аноним
10-05-2018
To find g(f(x)), plugin 3x - 2 into the x value of 2x-1
So,
2x - 1
2(3x-2) - 1
Now solve 2(3x-2) - 1
Use the distribution property
2 * 3x = 6x
2 * -2 = -4
2(3x-2) - 1
6x - 4 - 1
6x - 5
The answer is 6x - 5 = b
Answer Link
VER TODAS LAS RESPUESTAS ( 59+ )
Otras preguntas
The major evidence that changes have occurred in species is the: A. Domestication of animals B. Fossil record C. Mortality of individuals D. Variation among
If cos -105º = -0.26 and csc -105º = -1.03, then cos 105º = ? and csc 105º = ?
Which type of law is used to help solves disputes between people and organizations
Factor 60x-84 using the GCF. The factored expression is?
One reason the crusades failed to conquer the holy land permanently was because
Should i remove the plastic on finish dishwasher pods?
Which branch of government has the power to propose laws?
A farmer bought chickens and ducks to restock his farm. He also purchased milking cows for his wife’s milk-making enterprise. The total cost was $11425. He reme
nnnnnnnnnnnnn nnnnnn nnnnn
In the real numbers what is the solution of the equation 8^2x+1=4^1-x